The Effect of Soaking Time in Seasoning on the Quality of Squid Chips (Loligo Sp.) - Palilati, Rosita; Husain, Rahim; Yusuf, Nikmawatisusanti (European Journal of Life Safety and Stability (2660-9630), 2021)
This study aims to determine the effect of soaking time in seasoning on the panelists’ preference value and the chemical quality of squid chips (Loligo sp.). This study consisted of 2 stages, namely preliminary research to determine the appropriate seasoning soaking time in making chips and the results were used as a basis for consideration in the main research and main research to determine the characteristics of squid chips. The treatments in this study were soaking in seasoning for 1 hour, 2 hours and 3 hours. The hedonic score sheet data were designed using Kruskal Wallis and analyzed using K Independent Nonparametric Tests on the SPSS 16 device. The chemical data was designed using a Completely Randomized Design and analyzed with ANOVA on the SPSS 16 device. The data from the treatment results that had a significant effect were continued with Duncan’s further test. The results showed that the soaking time in seasoning had a significant effect on hedonic organoleptic analysis (aroma, taste and texture) and chemical analysis (moisture, ash and protein content) of squid chips. The results of chemical testing of squid chips have a water content of 28.345% - 32.70%, ash content of 2.26% - 3.24%, protein content of 56.64% - 58.86. Based on the standard of SNI 01-2602-1992 regarding tempe chips, in general, the water content does not meet the quality standard for fried tempe chips, namely the maximum water content of 3%.